Sodium-ion battery positive electrode material, preparation method thereof and sodium-ion battery containing sodium-ion battery positive electrode material
Through the preparation of Na47V30(PO4)35(P2O7)8 phosphate material and single-wall carbon nanotube composite material, a one-dimensional rod-like structure is formed, which solves the problem of low diffusion rate of sodium ions in the positive electrode material of sodium ion battery and achieves high magnification Performance and long-term cycle stability, and improved energy density and voltage platform.
Patent Information
- Application Number
- CN202411315158.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-17
AI Technical Summary
The diffusion rate of sodium ions in the positive electrode materials of sodium ion batteries is low, affecting device-level power density and cycling stability. The existing doping and nanostructure design methods have interfacial side reactions and load density problems, making it difficult to effectively improve performance.
Na47V30(PO4)35(P2O7)8 phosphate material is used to form a composite material with single-wall carbon nanotubes. Through ultrasonic treatment and polycarboxylic acid guidance, a one-dimensional rod-like structure is formed to accelerate sodium ions diffusion, and two stages are carried out at high temperature. Heat treatment is used to form a composite material with a oriented crystal plane.
It significantly improves the rate performance and cycle stability of the positive electrode material of sodium ion battery, achieves ultra-high rate performance up to 50C and cycle life of more than 5,000 times, and improves the energy density and voltage platform.
Smart Images

Figure CN119153684A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a sodium ion battery positive electrode material and a preparation method thereof and a sodium ion battery containing the positive electrode material. Background Art
[0002] Due to the abundant reserves of sodium on the earth, sodium-ion batteries (SIBs) are considered to be one of the promising next-generation energy storage devices. The cathode material plays a vital role in the performance of sodium-ion batteries. Common cathode materials for sodium-ion batteries include layered metal oxides, Prussian blue derivatives, and NASICON-type phosphate materials. Among them, layered metal oxides have the disadvantages of poor stability in air and unstable capacity performance; Prussian blue derivative cathode materials also have the disadvantages of difficulty in water removal, low cycle life, poor actual rate performance, low volume energy density, large voltage polarization, and the risk of thermal runaway; while NASICON-type phosphate materials, such as Na3V2(PO4)3 (abbreviated as NVP), have received widespread attention due to their strong three-dimensional framework and adjustable crystal structure.
[0003] However, sodium ions diffuse slowly within the crystal structure of NVP, which will seriously affect its rate performance and device-level power density as a cathode material. For example, under high-rate conditions, the slow diffusion of sodium ions will cause a concentration gradient from the surface to the center of the material, resulting in a high degree of polarization of the material, making the active material insufficiently utilized, and greatly reducing its energy and power density.
[0004] To solve this problem, heterogeneous atoms (such as K, Fe, Zn, etc.) are usually doped to improve the sodium ion conductivity of the positive electrode material. However, element doping may lead to changes in the crystal structure, which may affect the stability of the charge and discharge cycle, especially in the high rate process, this effect will be more significant. Other strategies include designing nanostructures to shorten the bulk transmission distance of sodium ions, or using amorphous or microcrystalline materials to introduce grain boundaries to achieve built-in high-speed sodium ion fast channels. However, nanomaterials have a larger specific surface area, which will lead to more interfacial side reactions, and the low loading density of the positive electrode material will affect the filling density of the sodium ion battery, and ultimately affect the energy density and specific capacity of the battery. Compared with the corresponding crystalline materials, the atomic groups of the amorphous phase in amorphous or microcrystalline materials have significantly different arrangements, which will change their reaction mechanism, and their reactivity and stability need to be further studied. Therefore, what measures should be taken to effectively improve the performance of NVP becomes the key to its practical application.
[0005] In addition, despite the stable crystal structure and high capacity of 117 mAh g-1 based on the extraction / insertion of two sodium ions, NVP -1 , but the solid phase ion diffusion kinetics and V 3+ / V4+ The redox voltage of NASICON is relatively low, about 3.3 V, which limits the realization of its high energy density. In the NASICON compound family, Na7V4(P2O7)4PO4 (abbreviated as NVPP) can not only provide a well-defined ion diffusion channel with a 3D framework structure, but also can transfer V to the ion matrix through the electron-attracting effect of the [P2O7] group. 3+ / V 4+ The redox voltage of NVPP was increased to about 3.87 V. More importantly, Na5V4(P2O7)4PO4 from NVPP could reduce the reaction barrier and induce better kinetics. Summary of the invention
[0006] The primary purpose of the present invention is to provide a sodium ion battery positive electrode material, so as to significantly improve the sodium ion diffusion rate in the sodium ion battery positive electrode and the positive electrode material rate performance, thereby improving the overall performance and long-term cycle stability of the sodium ion battery.
[0007] To achieve this object, in a basic embodiment, the present invention provides a sodium ion battery positive electrode material, wherein the sodium ion battery positive electrode material comprises a chemical formula of Na 47 V 30 (PO4) 35 (P2O7)8 phosphate material.
[0008] In a preferred embodiment, the present invention provides a sodium ion battery positive electrode material, wherein the sodium ion battery positive electrode material further comprises a single-walled carbon nanotube material, which is composed of a chemical formula of Na 47 V 30 (PO4) 35 A composite material formed by (P2O7)8 phosphate material and single-walled carbon nanotube material.
[0009] The second object of the present invention is to provide a method for preparing the positive electrode material of a sodium ion battery as described above, so as to better prepare the positive electrode material of a sodium ion battery as described above, and the prepared positive electrode material of a sodium ion battery can significantly improve the sodium ion diffusion rate in the positive electrode of the sodium ion battery and the rate performance of the positive electrode material, thereby improving the overall performance and long-term cycle stability of the sodium ion battery.
[0010] To achieve this object, in a basic embodiment, the present invention provides a method for preparing the positive electrode material for a sodium ion battery as described above, the preparation method comprising the following steps:
[0011] (1) mixing the raw materials for preparing the positive electrode material of the sodium ion battery including a sodium source material, a vanadium source material, and a phosphorus source material, and then adding deionized water to obtain a rheological material after a period of time;
[0012] (2) The rheological material is subjected to ultrasonic treatment, drying treatment and calcination treatment of the drying product to obtain the positive electrode material of the sodium ion battery.
[0013] In a preferred embodiment, the present invention provides a method for preparing a positive electrode material for a sodium ion battery as described above, wherein in step (1), the molar ratio of the sodium source material, the vanadium source material, and the phosphorus source material is (47-49):30:51.
[0014] In a preferred embodiment, the present invention provides a method for preparing a positive electrode material for a sodium ion battery as described above, wherein in step (1), the mass of the deionized water is 0.5-2% of the mass of the raw material for preparing the positive electrode material for a sodium ion battery.
[0015] In a preferred embodiment, the present invention provides a method for preparing a positive electrode material for a sodium ion battery as described above, wherein in step (1), the sodium source material is sodium carbonate, the vanadium source material is vanadium pentoxide, and the phosphorus source material is diammonium phosphate.
[0016] In a preferred embodiment, the present invention provides a method for preparing a positive electrode material for a sodium ion battery as described above, wherein in step (2), polycarboxylic acid and single-walled carbon nanotubes are added to the rheological substance before ultrasonic treatment.
[0017] In a preferred embodiment, the present invention provides a method for preparing the positive electrode material for a sodium ion battery as described above, wherein the polycarboxylic acid is citric acid and / or oxalic acid.
[0018] In a preferred embodiment, the present invention provides a method for preparing a positive electrode material for a sodium ion battery as described above, wherein in step (2), the mass ratio of the single-walled carbon nanotubes to the raw materials for preparing the positive electrode material for a sodium ion battery mixed in step (1) is (0.5-5):100.
[0019] In a preferred embodiment, the present invention provides a method for preparing a positive electrode material for a sodium ion battery as described above, wherein in step (2), the power of the ultrasonic treatment is 100-1000 W and the time is 0.3-1 h.
[0020] In a preferred embodiment, the present invention provides a method for preparing the positive electrode material for a sodium ion battery as described above, wherein in step (2), the drying treatment is carried out at a temperature of 110-130° C. and for a time of 10-15 h.
[0021] In a preferred embodiment, the present invention provides a method for preparing a positive electrode material for a sodium ion battery as described above, wherein in step (2), the calcination treatment is a two-stage heat treatment carried out under an argon protective atmosphere, the temperature of the first stage heat treatment is 330-370°C, and the time is 3-5 hours; the temperature of the second stage heat treatment is 730-770°C, and the time is 7-9 hours.
[0022] The third object of the present invention is to provide a sodium ion battery, which can significantly improve the sodium ion diffusion rate in the positive electrode of the sodium ion battery and the rate performance of the positive electrode material, thereby having better overall performance and long-term cycle stability.
[0023] To achieve this object, in a basic embodiment, the present invention provides a sodium ion battery, wherein the sodium ion battery comprises a sodium ion battery positive electrode made of the sodium ion battery positive electrode material as described above.
[0024] The beneficial effect of the present invention is that the sodium ion battery positive electrode material of the present invention can significantly improve the sodium ion diffusion rate in the sodium ion battery positive electrode and the positive electrode material rate performance, and the sodium ion battery made from the sodium ion battery positive electrode material has better overall performance and long-term cycle stability.
[0025] The present invention provides a novel sodium ion battery positive electrode material Na 47 V 30 (PO4) 35 (P2O7)8 (abbreviated as ZNVP), in which the synergistic effect of PO4 and P2O7 anion groups makes it have higher specific capacity and voltage platform, and therefore has higher energy density. In addition, through the detailed study of the preparation process of this material, a trace amount of deionized water is added to the raw material (sodium carbonate, vanadium pentoxide, ammonium dihydrogen phosphate, citric acid) powder to trigger the self-activation reaction of the raw materials, forming a rheological state between solid and liquid, and achieving the mixing of raw materials at the atomic level; in this process, single-walled carbon nanotubes (single-walled CNTs) are added, so that the reactants and single-walled CNTs are fully contacted and reacted in the original stage, and the one-dimensional single-walled CNTs guide the self-assembly of elements such as sodium, vanadium, and phosphorus; in the subsequent crystallization process, the self-activated assembled raw materials and the one-dimensional CNTs form a spontaneous crystal plane orientation, thereby forming a one-dimensional rod-shaped ZNVP / CNT composite material. The one-dimensional structure of ZNVP prepared by this method can greatly accelerate the diffusion dynamics of sodium ions, thus giving it an ultra-high rate performance of up to 50C; at the same time, the material also maintains the structural stability of the polyanion material and can achieve more than 5000 cycles.
[0026] The beneficial effects of the sodium ion battery positive electrode material ZNVP and the preparation method thereof provided by the present invention are specifically embodied in:
[0027] (1) ZNVP has a novel crystal structure, and PO4 and P2O7 work together to significantly improve the diffusion of sodium ions in the material and improve the rate characteristics of ZNVP; unlike other polyanion materials, such as the 3.3V platform caused by PO4 in Na3V2(PO4)3, and the 3.8V platform achieved by only the P2O7 group in Na7V4(P2O7)4PO4 (which also has a double anion group), the sodium ion battery positive electrode material ZNVP provided by the present invention has voltage platforms at both 3.3V and 3.8V, indicating that the two anion groups work together. In addition, compared with the mixture of Na3V2(PO4)3 and Na7V4(P2O7)4PO4, ZNVP has better rate performance.
[0028] (2) In the preparation method of the sodium ion battery positive electrode material ZNVP provided by the present invention, a self-activation reaction between raw materials is initiated by a trace amount of water, which can shorten the reaction time, increase the reaction rate and achieve atomic-level raw material mixing.
[0029] (3) In the preparation method of the sodium ion battery positive electrode material ZNVP provided by the present invention, the addition of one-dimensional CNTs will guide the reactants to be further evenly mixed and trigger the self-assembly of the raw materials, which is conducive to the formation of a one-dimensional rod-shaped ZNVP / CNT composite with a directional crystal plane orientation similar to the one-dimensional CNT during the subsequent high-temperature sintering process.
[0030] (4) In the one-dimensional rod-shaped ZNVP / CNT composite generated by the present invention, the one-dimensional CNT is cross-linked to form a three-dimensional conductive network, which is beneficial to improving the electronic conductivity of ZNVP; the special structure in the rod-shaped ZNVP material is beneficial to improving the ion transmission rate while shortening the ion diffusion path, thereby improving the ion transport properties of ZNVP. Different from other subsequent addition of conductive materials (such as CNT) solutions, in the present invention, CNT and ZNVP are in-situ composites, the two have a large contact area and chemical interaction between them, and can withstand volume changes during the charge and discharge process while maintaining good electron and ion transmission channels, so that the positive electrode material of the sodium ion battery has excellent low-rate characteristics and cycle stability throughout the life cycle.
[0031] (5) The one-dimensional rod-shaped ZNVP / CNT composite generated by the present invention has a small volume change during the charge and discharge process, and the one-dimensional CNT in-situ coating with high mechanical properties can stabilize the crystal structure of ZNVP during the charge and discharge process and improve the cycle stability of ZNVP. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is the SEM test result in Example 2.
[0033] Figure 2 This is the charge and discharge curve detection result in Example 2. DETAILED DESCRIPTION
[0034] In order to better understand the technical solutions and advantages of the present invention, the present invention is further described below through embodiments in conjunction with the accompanying drawings.
[0035] Example 1: Preparation of ZNVP sodium ion battery positive electrode material (I)
[0036] According to the amount of 0.001mol ZNVP prepared, V2O5, NH4H2PO4, and Na2CO3 powders were weighed in sequence according to the molar ratio of Na:V:P=47:30:51 and mixed evenly. Then, deionized water with a total mass percentage of 1% of the above raw materials (V2O5, NH4H2PO4, and Na2CO3) was added dropwise to the mixture. At this time, the raw material powders reacted spontaneously and released a large amount of gas, and a rheological substance was formed after about 30 minutes. Then, 10% citric acid and 2% single-walled CNT (TUBALL TM BATT H2O or Nanjing Muke MK2166, the same below). The mixture was ultrasonically treated for 0.5 h (ultrasonic power 300 W), and then dried in an oven at 120 ° C for 12 h, and the resulting product was preheated at 350 ° C in an argon atmosphere for 4 h, and then heated at 750 ° C for another 8 h to obtain the final ZNVP sodium-ion battery positive electrode material.
[0037] Example 2: Preparation of ZNVP sodium ion battery positive electrode material (II)
[0038] The amount of raw materials was weighed according to the molar ratio of Na:V:P=49:30:51, and the rest was consistent with Example 1.
[0039] Comparative Example 1: Preparation of NVP sodium ion battery positive electrode material
[0040] According to the amount of preparing 0.001 mol NVP, V2O5, NH4H2PO4, and Na2CO3 powders were weighed respectively according to the molar ratio of Na:V:P=3:2:3, and the rest was the same as Example 1 to obtain the final NVP sodium ion battery positive electrode material.
[0041] Comparative Example 2: Preparation of NVPP sodium ion battery positive electrode material
[0042] According to the amount of preparing 0.001 mol NVPP, V2O5, NH4H2PO4, and Na2CO3 powders were weighed respectively according to the molar ratio of Na:V:P=7:4:9, and the rest was the same as Example 1 to obtain the final NVPP sodium ion battery positive electrode material.
[0043] Comparative Example 3: Preparation of NVP+NVPP sodium ion battery positive electrode material
[0044] The sodium ion battery positive electrode materials prepared in Comparative Example 1 and Comparative Example 2 were ground and mixed in a mass ratio of 68.55:31.45 to obtain NVP+NVPP sodium ion battery positive electrode material.
[0045] Comparative Example 4: Preparation of MNVP sodium ion battery positive electrode material
[0046] MNVP is a mixture of NVP and NVPP synthesized in situ, with a mass ratio of 68.55:31.45. According to the amount of 0.001 mol MNVP, NH4VO3 and oxalic acid are weighed in a molar ratio of 1:2 and dissolved in deionized water, and stirred continuously until completely dissolved. Then, NH4H2PO4, Na2CO3 and single-walled CNTs accounting for 2% of the mass fraction of the raw materials (NH4VO3, NH4H2PO4, Na2CO3) are added to the above solution in sequence, and the mixture is stirred and dissolved. The mixture is ultrasonically treated for 0.5 hours (ultrasonic power 300W), then dried in an oven at 120°C for 12 hours, and the resulting product is preheated in an argon atmosphere at 350°C for 4 hours, and then heated at 750°C for another 8 hours to obtain the final MNVP sodium-ion battery positive electrode material.
[0047] Comparative Example 5: Preparation of R-MNVP sodium ion battery positive electrode material
[0048] R-MNVP is a mixture of NVP and NVPP synthesized in situ, with a mass ratio of 68.55:31.45. According to the amount of 3g MNVP, NH4VO3, NH4H2PO4, and Na2CO3 powders are weighed in turn and mixed evenly, and then deionized water with a total mass of 1% of the above raw materials (NH4VO3, NH4H2PO4, Na2CO3) is added to the mixture. After about 30 minutes, 10% of citric acid and 2% of single-walled CNT are added. The mixture is ultrasonically treated for 0.5 hours (ultrasonic power 300W), then dried in an oven at 120°C for 12 hours, and the resulting product is preheated in an argon atmosphere at 350°C for 4 hours, and then heated at 750°C for another 8 hours to obtain the final MNVP sodium-ion battery positive electrode material.
[0049] Comparative Example 6: Preparation of R-ZNVP sodium ion battery positive electrode material
[0050] According to the amount of 0.001mol ZNVP, V2O5 and citric acid are weighed in turn and dissolved in deionized water (the amount of citric acid is 10% of the mass fraction of the raw materials), and stirred continuously until completely dissolved. Then, NH4H2PO4, Na2CO3 and single-walled CNTs accounting for 2% of the mass fraction of the raw materials (V2O5, NH4H2PO4, Na2CO3) are added to the above solution in turn, and the mixture is stirred and dissolved. The mixture is ultrasonically treated for 0.5 hours (ultrasonic power 300W), then dried in an oven at 120°C for 12 hours, and the resulting product is preheated in an argon atmosphere at 350°C for 4 hours, and then heated at 750°C for another 8 hours to obtain the final R-ZNVP sodium ion battery positive electrode material.
[0051] Comparative Example 7: Preparation of G-ZNVP sodium ion battery positive electrode material
[0052] The amount of raw materials was weighed according to the molar ratio of Na:V:P=51:30:51, and the rest was the same as in Example 1.
[0053] The sodium ion battery positive electrode materials obtained in the above Examples 1-2 and Comparative Examples 1-7 were subjected to relevant tests, and the results are as follows.
[0054] The SEM test results of the sodium ion battery positive electrode materials obtained in Example 1 and Comparative Examples 4-6 are as follows: Figure 1 As shown. Figure 1 It can be seen that Example 1 generates a one-dimensional rod-shaped ZNVP / CNT composite with directional crystal plane orientation due to the self-activation and self-assembly reaction of raw materials with specific composition and proportion; Comparative Examples 4-6 have insufficient one-dimensional rod-shaped structure due to the lack of self-activation and self-assembly reaction or improper composition and proportion of raw materials.
[0055] The results of the charge and discharge curve test (refer to DOI:10.1016 / j.est.2024.112358 to prepare the battery and perform charge and discharge performance testing) are as follows Figure 2 As shown, it means that ZNVP exhibits a different charge and discharge platform and platform specific capacity from NVP, NVPP, and MNVP. Since the voltage platform is closely related to the electrochemical reaction and material structure, ZNVP has a completely different structure from the comparative example.
[0056] The results of electrochemical performance testing (refer to DOI: 10.1016 / j.est.2024.112358 to prepare batteries and perform electrochemical performance testing) are shown in Table 1 below.
[0057] Table 1 Electrochemical performance test results
[0058]
[0059] The results in Table 1 show that:
[0060] (1) ZNVP has the highest discharge specific capacity and the highest energy density at a low rate of 0.5C (thanks to its high voltage platform), and still maintains the highest specific capacity and energy density even at a high rate of 50C.
[0061] (2) It can be seen from the comparison between Example 1 and Comparative Example 4 that, thanks to its self-activation preparation method and the synergistic effect of PO4 and P2O7 in the material, ZNVP has significant advantages in specific capacity, rate characteristics, and energy density, indicating the superiority of ZNVP.
[0062] (3) The comparison between Example 1 and Comparative Example 5 shows that even if MNVP is prepared by the preparation method of Example 1, its performance still cannot reach that of ZNVP due to different components.
[0063] (4) The comparison between Example 1 and Comparative Example 6 shows that, although the same raw materials and proportions are used, the performance is still different due to the different preparation methods, which indicates that the preparation method of Example 1 is superior.
[0064] (5) Comparative Example 6 shows that despite the improper preparation method, ZNVP still has significant advantages in specific capacity, rate and energy density.
[0065] (6) Example 2 shows that appropriately increasing the input amount of Na-containing raw materials can help compensate for the Na loss during high-temperature sintering and improve the ZNVP specific capacity; however, if it is increased too much (Comparative Example 7), impurities may be generated, resulting in a decrease in performance such as specific capacity, rate, and energy density.
[0066] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these changes and variations. The above embodiments or implementations are merely illustrative of the present invention, and the present invention may also be implemented in other specific ways or other specific forms without departing from the gist or essential features of the present invention. Therefore, the described implementations should be considered illustrative rather than restrictive in any respect. The scope of the present invention should be described by the appended claims, and any changes equivalent to the intent and scope of the claims should also be included within the scope of the present invention.
Claims
1. A sodium ion battery positive electrode material, characterized in that: The sodium ion battery positive electrode material comprises a chemical formula of Na 47 V 30 (PO4) 35 (P2O7)8 phosphate material.
2. The sodium ion battery positive electrode material according to claim 1, characterized in that: The sodium ion battery positive electrode material also includes a single-walled carbon nanotube material, which is composed of a chemical formula of Na 47 V 30 (PO4) 35 A composite material formed by (P2O7)8 phosphate material and single-walled carbon nanotube material.
3. A method for preparing a positive electrode material for a sodium ion battery according to claim 1, characterized in that: The preparation method comprises the following steps: (1) mixing the raw materials for preparing the positive electrode material of the sodium ion battery including a sodium source material, a vanadium source material, and a phosphorus source material, and then adding deionized water to obtain a rheological material after a period of time; (2) The rheological material is subjected to ultrasonic treatment, drying treatment and calcination treatment of the drying product to obtain the positive electrode material of the sodium ion battery.
4. The preparation method according to claim 3, characterized in that: In step (1), The molar ratio of the sodium source material, the vanadium source material, and the phosphorus source material is (47-49):30:51; The mass of the deionized water is 0.5-2% of the mass of the raw material for preparing the positive electrode material of the sodium ion battery.
5. The preparation method according to claim 3, characterized in that: In step (1), the sodium source material is sodium carbonate, the vanadium source material is vanadium pentoxide, and the phosphorus source material is ammonium dihydrogen phosphate.
6. The preparation method according to claim 3, characterized in that: In step (2), polycarboxylic acid and single-walled carbon nanotubes are added to the rheological material before ultrasonic treatment.
7. The preparation method according to claim 6, characterized in that: The polycarboxylic acid is citric acid and / or oxalic acid.
8. The preparation method according to claim 6, characterized in that: In step (2), the mass ratio of the single-walled carbon nanotubes to the raw materials for preparing the sodium ion battery positive electrode material mixed in step (1) is (0.5-5):
100.
9. The preparation method according to claim 3, characterized in that: In step (2), The power of the ultrasonic treatment is 100-1000W, and the time is 0.3-1h; The drying process is carried out at a temperature of 110-130°C and a time of 10-15 hours; The calcination treatment is a two-stage heat treatment carried out under an argon protective atmosphere, wherein the temperature of the first stage heat treatment is 330-370°C and the time is 3-5 hours; the temperature of the second stage heat treatment is 730-770°C and the time is 7-9 hours.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises a sodium ion battery positive electrode made from the sodium ion battery positive electrode material according to claim 1 or 2.
